CARACTERIZAÇÃO MECÂNICA E TRANSIÇÃO FRÁGIL-DÚCTIL EM MATERIAIS VITROCERÂMICOS - Mathias, Ivan (2015)
In this work two vitreous systems are studied, the lithium disilicate (LS2) and sodiumcalcium-silica with stoichiometry 2Na2O.CaO.3SiO2 (2N1C3S) and the glassceramics formed from these by heat treatment. Several properties were determined for the two systems as a function of crystallized volume fraction, from glass to fully crystallization (100%), highlighting the fracture toughness and the brittle-ductile transition, with the last two determined only for the LS2 glass-ceramic. Hardness and elastic modulus were obtained for the two glass-ceramics and their values increase with the crystallized volume fraction in the glass ceramic, with the exception of hardness of 2N1C3S, which has its maximum for the crystallized volume fraction of 9%. Thermal expansion coefficients were determined and are larger in the LS2 glassy phase and in the 2N1C3S crystalline phase, thereby generating mean residual stresses obtained by Selsing model of -76 MPa for the LS2 (compression in the crystal) and 232 MPa for the 2N1C3S (traction in the crystal). The indentation fracture toughness was also determined for the two systems using the Anstis' and Niihara's models. The results show an increase of indentation fracture toughness with the crystalline volume fraction for LS2 glass-ceramic and also a dependence with indentation load. As for the 2N1C3S glass-ceramic, indentation fracture toughness are reduced at intermediate crystalline fractions, which is attributed to residual stresses arising from the difference between the thermal expansion mismatch between the glass and the crystalline phases. LS2 glass-ceramic flexural strength increases with the crystalline fraction, from 103 ± 3 MPa for the glass to 260 ± 20 MPa for the fully crystallized sample. Without the removal of the crystallization surface layer, this value rises to 290 ± 20 MPa. The increase in flexural strength in the first 20% of the crystallized fraction is more pronounced. As the size of the precipitates was kept constant, this increase can be related only to the increase in the crystallized fraction. The residual stress in the matrix, the critical radius of spontaneous cracking of the crystals and the crack mean free path between the precipitates were considered in the analysis of the increase in flexural strength. The existence of pores in the samples was a factor that limited its resistance. The fracture toughness (KDTIC) a function of the crystallized fraction was determined for LS2 glassceramics using the double torsion technique. It was found that KDTIC increases with the crystallized fraction, from 0.75 MPa.m1/2 for the glass to about 3.50 ± 0.05 MPa.m1/2 for the fully crystallized sample, a significant increase of approximately five times. Several factors were analyzed as possible causes of the increase in KDTIC. The experimental data are better adjusted with a recently proposed model with one adjustable parameter that relates the ratio of the crystal and glass areas to the crystallized volume fraction. The brittle-ductile transition (BDT) of LS2 glass and glass-ceramic samples (39% crystallized volume fraction) were determined for three different strain rates. BDT temperatures were determined for each strain rate.Activation energies of BDT for the glass and glass-ceramic were obtained, which were 5.2 ± 0.2 eV and 7 ± 2 eV. It was found that BDT activation energy in glass resembles the activation energy of the LS2 viscous flow, thus concluding the BDT in LS2 is governed by viscous flow of the glass matrix. Finally, the fact of the activation energy of the glass ceramic be larger than the glass was attributed to the fact that the viscosity of the vitreous matrix is "hindered" by the presence of crystalline precipitates. A viscosity model of a rigid spheres composite was used as an analogy to explain this observation.